Combating modern methods of legalisation (laundering) of the funds obtained by criminal means with the use of cryptocurrency - V. Р. Yatsenko; V. S. Bushyn (Bulletin of Kharkiv National University of Internal Affairs)
The problems of combating corruption have not lost their relevance over the years. Tolerant attitudes to corruption as a way to quickly solve everyday problems give rise to new ways of developing illegal activities in various spheres of public life. At the same time, while fully condemning corruption as a means of illicit enrichment, the majority of the population still follows the old path. Consequently, the interests of individuals aimed at enriching themselves by any means, including illegal means, are becoming a counterweight to the development of society.